2018
DOI: 10.1007/s00330-018-5438-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative correlation between uptake of Gd-BOPTA on hepatobiliary phase and tumor molecular features in patients with benign hepatocellular lesions

Abstract: • Gd-BOPTA uptake on HBP correlates with the OATP level in benign hepatocellular tumors • FNH and β-catenin-mutated HCA showed an increased lesion-to-liver contrast enhancement ratio (LLCER) • Increased LLCER may be explained by activation of the Wnt β-catenin pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…However, this series did not include all subtypes. Recently, Reizine et al reported similar results with a signal intensity quantitative analysis on Gd‐BOPTA imaging . Since high‐risk HCA showed a hyperintense signal on the HBP of Gd‐EOB‐DTPA‐enhanced MR images in our study, the radiological differentiation from hyperintense FNH should also rely on other MRI features, such as the heterogeneous “periseptal” uptake of FNH on HBP, the presence of a central scar or other MR phases features.…”
Section: Discussionsupporting
confidence: 79%
“…However, this series did not include all subtypes. Recently, Reizine et al reported similar results with a signal intensity quantitative analysis on Gd‐BOPTA imaging . Since high‐risk HCA showed a hyperintense signal on the HBP of Gd‐EOB‐DTPA‐enhanced MR images in our study, the radiological differentiation from hyperintense FNH should also rely on other MRI features, such as the heterogeneous “periseptal” uptake of FNH on HBP, the presence of a central scar or other MR phases features.…”
Section: Discussionsupporting
confidence: 79%
“…On the contrary, molecular studies have shown that OATP expression is persistent in b-HCA. 32 In the study of Ba-Ssalamah et al, five out of the six b-HCAs displayed retention of gadoxetic acid on the hepatobiliary phase. 31 This second example based on the history of HCA illustrates a second type of rad-path relationship: pathological references that are constantly changing and improving lead to continuous radiological progress.…”
Section: The Example Of Hepatocellular Adenomamentioning
confidence: 94%
“…31 This is in contradiction to the molecular background of I-HCA, as their OATP expression has been shown to be lower than that of the adjacent liver. 32 The explanation probably lies in the surrounding liver parenchyma, which frequently displays marked steatosis that modifies the relative signal intensity of tumors. On the contrary, molecular studies have shown that OATP expression is persistent in b-HCA.…”
Section: The Example Of Hepatocellular Adenomamentioning
confidence: 99%
“…Recent studies have confirmed that this lesion can be virtually indistinguishable from FNH and can show hepatobiliary hyperintensity; so appropriate clinical context can sometimes aid in distinction [22,23]. This hepatobiliary hyperintensity correlates with the organic anion transporting polypeptide (OATP) level in benign hepatocellular [22]. With inflammatory subtype lesions (25-35% adenomas), an ''atoll'' sign with T2-weighted MRI sequences has been described, denoting hyperintense T2 signal about the periphery and centrally within the lesion.…”
Section: Hepatocellular Adenomamentioning
confidence: 94%
“…No specific imaging signature has been ascribed to the beta-catenin-activated subtype (10-15% adenomas); these lesions may demonstrate any number of features, including varying degrees of enhancement at multiphase imaging, excretion of hepatobiliary contrast agents, and/or presence of a central fibrous scar. Recent studies have confirmed that this lesion can be virtually indistinguishable from FNH and can show hepatobiliary hyperintensity; so appropriate clinical context can sometimes aid in distinction [22,23]. This hepatobiliary hyperintensity correlates with the organic anion transporting polypeptide (OATP) level in benign hepatocellular [22].…”
Section: Hepatocellular Adenomamentioning
confidence: 94%